1989
DOI: 10.1128/jb.171.5.2882-2885.1989
|View full text |Cite
|
Sign up to set email alerts
|

Expression and inducibility in Staphylococcus aureus of the mecA gene, which encodes a methicillin-resistant S. aureus-specific penicillin-binding protein

Abstract: A beta-lactam-sensitive strain of Staphylococcus aureus could be converted to methicillin resistance by the introduction of a plasmid carrying the 4.3-kilobase HindIII chromosomal DNA fragment which encoded the mecA gene from a methicillin-resistant S. aureus. Transformant cells produced methicillin-resistant S. aureus-specific penicillin-binding protein constitutively, and additional insertion of an inducible penicillinase plasmid caused production of the pencillin-binding protein to become inducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
150
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(153 citation statements)
references
References 18 publications
1
150
0
2
Order By: Relevance
“…1 The mainstay of treatment has been the use of systemic and localized antibiotics. However, bacteria responsible for these infections continue to evolve resistance to commonly used antibiotics (i.e., methicillin) 2 and clearance of polymicrobial infection in patients can be difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The mainstay of treatment has been the use of systemic and localized antibiotics. However, bacteria responsible for these infections continue to evolve resistance to commonly used antibiotics (i.e., methicillin) 2 and clearance of polymicrobial infection in patients can be difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this study were to (1) characterize the ability of antibiotic-loaded absorbable, synthetic, high-purity calcium sulfate (Stimulan Rapid Cure, Biocomposites, Keele, U.K.) beads to clear bacteria in liquid and plate cultures of gram-negative and grampositive cultures, (2) to compare the elution of antibiotics from calcium sulfate against PMMA (Simplex P, Stryker, Kalamazoo, MI) using the disc diffusion assay method for antimicrobial susceptibility testing, and (3) examine the structural differences between how these materials bind antibiotics as this will impact their ability to elute the drug after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the transpeptidase activity of PBP2a is functional at normally inhibitory concentrations of beta-lactam antibiotics, allowing cell wall synthesis to occur (2)(3)(4). Recently, a novel variant of mecA was identified in Staphylococcus aureus from cattle (5), humans, and a range of other animal species (6) in Denmark, France, The Netherlands, Ireland, Germany, Belgium, and the United Kingdom (5,(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It has been established that the production of an additional penicillin-binding protein PBP-2' (PBP-2a), with low-affinity for betalactam antibiotics, is mainly involved in the mechanism of methicillin resistance of S. aureus [3]. While the PBP-2', which is encoded by a chromosomal structural gene designated as mecA, is usually induced by beta-lactam antibiotics, it is known to be constitutively produced in some MRSA [4,5]. Further epidemiological studies revealed that mecA genes are also distributed widely among CNS, and are associated with methicillin-resistance [6][7][8].…”
Section: Introductionmentioning
confidence: 99%